Inter-Religious Relations in the Period of Prophet Muhammad - Patmawati Patmawati (Graduate Program of Pontianak Institute of Islamic Studies, 2016)
Inter-religious relations in the period of Prophet Muhammad were running in harmony. Although there were theological differences between some religious faiths, these differences do not detract good relations. One of the written evidence of the condition of inter-religious harmony in this period was the agreement to live in peace as outlined in a treaty to respect and protect. The Madina Charter is proof that Prophet Muhammad was a religious leader as well as a political leader. The Madina Charter was born ahead of its time and can be used as a source of inspiration for building a plural society. Through the Medina Charter, the Prophet successfully organized all ethnic and religious groups in Medina, uniting them as brothers, despite different religious and ethnic backgrounds, all having the same duty to defend the State of Medina should there be an attack from outside. As a work which is based on literature research project, this article shows that the discussion of inter-religious relations in the period of Prophet Muhammad were not only supported by the works of schoolars in the fields of history and other related fields but also by the religiously based texts.